Randomized Comparison of the Crush Versus the Culotte Stenting for Coronary Artery Bifurcation Lesions - Zheng, Xu-Wei (Chin Med J (Engl), 2016)
BACKGROUND: The crush and the culotte stenting were both reported to be effective for complex bifurcation lesion treatment. However, their comparative performance remains elusive. METHODS: A total of 300 patients with coronary bifurcation lesions were randomly assigned to crush (n = 150) and culotte (n = 150) treatment. The primary endpoint was the occurrence of major adverse cardiac events (MACEs) at 12 months including cardiac death, myocardial infarction, stent thrombosis, and target vessel revascularization. Index lesion restenosis at 12 months was a secondary endpoint. The surface integrals of time-averaged wall shear stress at bifurcation sites were also be quantified. RESULTS: There were no significant differences in MACE rates between the two groups at 12-month follow-up: Crush 6.7%, culotte 5.3% (P = 0.48). The rates of index lesion restenosis were 12.7% versus 6.0% (P = 0.047) in the crush and the culotte groups, respectively. At 12-month follow-up, the surface integrals of time-averaged wall shear stress at bifurcation sites in the crush group were significantly lower than the culotte group ([5.01 ± 0.95] × 10(−4) Newton and [6.08 ± 1.16] × 10(−4) Newton, respectively; P = 0.003). CONCLUSIONS: Both the crush and the culotte bifurcation stenting techniques showed satisfying clinical and angiographic results at 12-month follow-up. Bifurcation lesions treated with the culotte technique tended to have lower restenosis rates and more favorable flow patterns.